Epidemiologia das infecções por nematódeos gatrintestinais em ovinos criados em Botucatu - Wilmsen, Maurício Orlando [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The epidemiology of gastrointestinal nematode infections was evaluated in sheep raised in Botucatu – SP. Every month, from April 2008 until March 2011, two tracer lambs were exposed to natural infection with gastrointestinal nematodes for 28 consecutive days, while grazing together with a sheep flock. Haemonchus contortus presented the highest infection intensities with 100% prevalence. There was no significant influence of the seasons in H. contortus infection intensity. Trichostrongylus colubriformis also presented 100% prevalence with the lowest infection intensity during the summer months. In the case of T. colubriformis, there was significant correlation coefficient between worm counts x precipitation (r = -0.32; P < 0.05). Other three nematodes species were found in tracer lambs, however, in small numbers. Their prevalence and mean intensity of infection (in parenthesis) were the following: Oesophagostomum columbianum 28% (25.2), Cooperia curticei 7% (4.5) and Trichuris spp. 2% (1). In conclusion, the environmental conditions of the area were very favourable for H. contortus and T. colubriformis transmission all year round. These explain in part the failure of private and governmental programs to promote the sheep breeding activity in São Paulo State due to high sheep mortality rates and low productivity caused by gastrointestinal nematode infections

A epidemiologia das infecções por nematódeos gastrintestinais foi avaliada em ovinos criados em Botucatu - SP. A partir de abril de 2008 até março de 2011, dois cordeiros traçadores foram expostos à infecção natural por nematódeos gastrintestinais durante 28 dias consecutivos, ao pastejar junto com um rebanho de ovelhas. Haemonchus contortus apresentou as maiores intensidades de infecção com prevalência de 100%. Não houve influência significativa das estações do ano na intensidade de infecção por H. contortus. Trichostrongylus colubriformis também apresentou prevalência de 100% com a intensidade de infecção menor durante os meses de verão. No caso de T. colubriformis, houve correlação significativa entre as contagens de vermes x precipitação (r = -0,32; P < 0,05). Outras três espécies de nematódeos foram verificadas, no entanto, em pequenas quantidades, prevalências e intensidades de infecção: Oesophagostomum columbianum 28% (25,2), Cooperia curticei 7% (4,5) e Trichuris spp. 2 % (1). Contudo, as condições ambientais da área foram favoráveis durante todo o ano para a transmissão de H. contortus e T. colubriformis. Este fato explica parcialmente o fracasso de programas governamentais e privados realizados no intuito de promover a ovinocultura no Estado, devido a taxas elevadas de mortalidade e baixa produtividade causada pela verminose
Keywords: Sistema gastrointestinal - Doenças; Haemonchus contortus; Estudos transversais; Epidemiologia veterinaria; Ovino - Doenças - Influência do clima; Gastrointestinal system Diseases; Botucatu (SP)